PENGARUH MEDIA AUDIOVISUAL TERHADAP ENGAGEMENT DAN MINAT BELAJAR PAI DI SEKOLAH MENENGAH - Muhammad Subhan; Nur Afifah; Abu Amar; Zuhriyyah Hidayati (Rihlah Review: Jurnal Pendidikan Islam, 2025)
This research aims to examine the influence of audiovisual media usage on students' learning interest in Islamic Religious Education (PAI) at SMP Simanjaya, particularly among eighth-grade students in the academic year 2024/2025. The learning process in schools demands effective teaching approaches that can increase motivation and student involvement. Audiovisual media, integrating sound and visual elements, are predicted to improve students' attention, enjoyment, and engagement in learning activities. This quantitative study uses questionnaires, observations, and documentation to gather data. A total of 30 students participated as the research population. Data analysis includes descriptive statistics and inferential analysis, including validity tests, reliability, normality, linearity, and simple regression analysis. The results indicate that audiovisual media were used frequently by teachers, reaching 80% in frequency percentage within a week. Students’ learning interest also reached 70% in frequency percentage. Regression analysis shows that audiovisual media have a moderate influence on learning interest, with a determination value of 0.188. These findings demonstrate that audiovisual media significantly contribute to improving students' learning interest in PAI learning.